2014
DOI: 10.1038/nrc3847
|View full text |Cite
|
Sign up to set email alerts
|

The TAM family: phosphatidylserine-sensing receptor tyrosine kinases gone awry in cancer

Abstract: The TYRO3, AXL (also known as UFO) and MERTK (TAM) family of receptor tyrosine kinases (RTKs) are aberrantly expressed in multiple haematological and epithelial malignancies. Rather than functioning as oncogenic drivers, their induction in tumour cells predominately promotes survival, chemoresistance and motility. The unique mode of maximal activation of this RTK family requires an extracellular lipid–protein complex. For example, the protein ligand, growth arrest-specific protein 6 (GAS6), binds to phosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
687
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 594 publications
(698 citation statements)
references
References 193 publications
8
687
0
3
Order By: Relevance
“…RTKs include 20 families that are distinguished by amino acid sequence identity within the kinase domain and exhibit structural similarities within their extracellular regions [5]. This review focuses on the TAM family, which is one of the latest to evolve and last to be identified [2,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…RTKs include 20 families that are distinguished by amino acid sequence identity within the kinase domain and exhibit structural similarities within their extracellular regions [5]. This review focuses on the TAM family, which is one of the latest to evolve and last to be identified [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…The TAM family includes three receptors, tyrosine kinase receptor 3 (Tyro3), Axl, and Mer, which share the vitamin K-dependent ligands, growth arrest-specific protein 6 (Gas6) and protein S. Gas6 binds all three TAM receptors, and protein S binds only Tyro3 and Mer [2,6]. The most prevalent functions of the TAM family and their ligands were investigated in tumour genesis [2,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Externalized PS is also a well-characterized cell marker that is primarily responsible for the recognition and uptake of dying apoptotic cells by phagocytes and for quelling potential autoimmune responses (28). Activation of phagocytic cells is mediated by the interaction of PS with the TAM (TYRO3, AXL, and MERTK) and TIM (T-cell immunoglobulin and mucin) families of PS receptors that induce expression of immune suppressive cytokines, dampen inflammatory signaling mechanisms, and inhibit innate immune cellular responses (29)(30)(31). Tumor vasculature-endothelial cells (32,33), tumor-derived microvesicles (34), and tumor cells all exhibit PS-mediated "apoptotic mimicry" to suppress proinflammatory antitumor immune responses (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%